2018
DOI: 10.1002/pssb.201800391
|View full text |Cite
|
Sign up to set email alerts
|

Interface State Luminescence and Sub‐Bandgap Absorption Based on CuGaO2 Nanoplates/ZnO Nanowires Heterostructure Arrays

Abstract: In this paper, the vertical arrays of ZnO nanowires (NWs) are uniformly grown on the surface of hexagonal CuGaO2 (CGO) nanoplates (NPs) through the hydrothermal method, forming the high‐density p–n heterojunction. The photoluminescence (PL) properties of these hetero‐assembled structures are characterized, and an obvious ultraviolet (UV) emission centered at 392.32 nm has been observed. Compared with the PL spectra of pure ZnO NWs, the UV peak red‐shift occurred and the spectrum broadened almost 2.5 times. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…After the dense vertical ZnO NWs arrays grown on the CGO NP S , a red‐shift appears in the PL spectrum and the FWHM have been broadened obviously which compared with the pure ZnO NWs. According to our previous works, this phenomenon could be attributed to the interface recombination between the CGO NPs and ZnO NWs . As the heterojunctions structure synthesized, a built‐in electric field will be established through carrier diffusion, resulting in band bending at interface.…”
Section: Resultsmentioning
confidence: 90%
“…After the dense vertical ZnO NWs arrays grown on the CGO NP S , a red‐shift appears in the PL spectrum and the FWHM have been broadened obviously which compared with the pure ZnO NWs. According to our previous works, this phenomenon could be attributed to the interface recombination between the CGO NPs and ZnO NWs . As the heterojunctions structure synthesized, a built‐in electric field will be established through carrier diffusion, resulting in band bending at interface.…”
Section: Resultsmentioning
confidence: 90%
“…Assuming the complete ionization of the acceptors at room temperature, the hole concentration will also increase to this value. Shi and her team also reported a hole concentration of 10 14 cm –3 for CGO nanoplates synthesized by a hydrothermal method . On the other hand, Bredar et al synthesized CGO nanocrystals by the hydrothermal method and examined the production by XPS and electrochemical impedance spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…CGO is also used as photoanode in the dye-sensitized solar cells (DSSCs) . In addition, the use of this substance as a hole transport layer (HTL) in perovskite solar cells has appeared very promising. , Due to the suitable electronic, optical, and chemical properties of CGO, it can also be used in p-channel transparent thin-film transistors (TTFTs), photocatalysts, p–n junctions, UV emitting diodes, H 2 generation, and photodetectors . However, the use of CGO in electronic and electro-optical devices requires the proper electronic connection between this semiconductor and a suitable metal, which always faces challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The Ga source materials were dissolved in nitrate or acetylacetonate sols, and the lms prepared with acetylacetonate had a higher transmittance than those prepared with nitrate. Xu et al [15] reported the formation of ZnO nanowires with n-type semiconductor properties on the surface of p-type delafossite, CuGaO 2 . The multihorned composites of hexagonal CuGaO 2 and ZnO nanowires were successfully fabricated by a hydrothermal method.…”
Section: (Iii))mentioning
confidence: 99%